Treatment and ophthalmic sequelae in a horse with facial cellulitis and orbital abscess. (16th November 2016) - Racine, J.; Borer‐Germann, S. E.; Navas de Solis, C.; Stoffel, M. H.; Klopfenstein, M.; Klopfenstein Bregger, M. D.
Summary: A 22‐year‐old Quarter Horse gelding with a history of dental (107) extraction 2 weeks previously was presented with facial cellulitis and an orbital abscess. The abscess was drained surgically dorsally and ventrally to the zygomatic arch and the horse was treated with parenteral antimicrobial and anti‐inflammatory drugs. The affected eye was protected with a temporary tarsorrhaphy and treated via a subpalpebral catheter. Six months after presentation, the horse was in excellent general condition and returned to previous level of exercise but showed blindness on the affected side. Pallor of the optic disc and severe attenuation of the retinal vessels, suggestive of optic disc atrophy, were present.